Management practices as correlates of information and communication technology use for health education delivery among practitioners in Oyo State Nigeria (2017)
Health education is a proven cost effective disease prevention strategy. Effective health education delivery to heavy disease- burden-carrying- community people depends largely on the use of Information and Communication Technology (ICT). This study therefore examined management practices as correlates of information and communication technology use for health education delivery among practitioners in Oyo State, Nigeria. A descriptive survey research design was adopted for the study. The population was all community health practitioners in Oyo State. The instrument used for data collection was a self-constructed questionnaire with 0.87 reliability coefficient The collected data were analysed using Pearson's Product- Moment Correlation, Analysis of Variance and Regression statistics. Findings show that variables of management practices correlated significantly with effective health education delivery. It was concluded that good management practices can enhance use of Information and Communication technology in the delivery of health education. Therefore, it is recommended that infrastructure maintenance, personnel training, usage of monitoring and supporting policy that can facilitate the use of ICT by community health practitioners to deliver health education effectively should be put in place.